Factors affecting the usage of social CRM applications - Can, Mehmet Nuri. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2013., 2013)
Improvements on internet changed many things in our lives and social media is one of the important changes that happenED. Today, several people spend significant amount of time on social networking sites. This situation also affected business. Customer relationship management (CRM), which is a quite popular concept in the professional world, strategies of companies started to change and they wanted to adopt new technologies to their existing daily activities with the consumers. This is how Social CRM, another new concept, emerged. In this study, factors affecting social CRM applications usage in Turkey has been researched. Eight potential factors determined by examining the extant literature and the results show that consumers’ existing relationship with brand interacted and their privacy and security concerns are the most influential issues for Turkish consumers’ social CRM applications usage.
Keywords: Customer relations.; Relationship marketing.